Kościół katolicki wobec pamięci zbiorowej Polaków. Ciągłość i zmiana - Stachowiak, Paweł (Przegląd Politologiczny, 2018)
The paper attempts to present the leading objectives and motives of the ‘Church’s policy of memory’ before and after 1989. The author states that, like many other institutions of public life, the Catholic Church implements its own policy to shape the collective memory of Poles, both in terms of legitimization and content. At the time of the Polish People’s Republic, the first and foremost objective of the ‘Church’s memory policy’ was to counteract the activities of the communist authorities, which were carrying out a project to restrict the Church’s influence to the narrowly understood field of the priesthood and which ultimately aimed at the atheization of Polish society. The emphasis on the historical symbiosis of Polishness and Catholicism served the purpose of defending the traditional form of Polish religiousness and providing the Church with social support in the struggle to maintain the public dimension of its influence. Despite the change in language, the present objective of the Church’s historical narration appears similar: to oppose these aspects of secularization trends that drive the Church away from public space and so intensifying the phenomenon of the privatization of faith. Whether in the past or present, the Church’s vision of the past is to secure its own stability as an institution and retain the role of a significant factor contributing to the national and state conscience of Poles.